Analisis Minat Wisatawan terhadap Wisata Kuliner Waroeng Semawis Kota Semarang - Hanif Salsabila; Maruto Umar Basuki (Universitas Diponegoro, 2020)
Semarang City has the potential to become a tourist destination because it has authentic culture and a multicultural society. But its development is still lagging behind other regions. According to Mayang (2017), this is due to less optimal management of the Semarang City tourism sector. One of the tourist attraction that deserves to be developed is culinary tourism Waroeng Semawis Semarang City culinary tour. This study aims to determine the spesialization characteristics of tourist in culinary tourism Waroeng Semawis Semarang based on age, gender and education. Analysis methods in this research are descriptive analysis, factor analysis, crosstab anaylsis and variant analysis. The result of this research indicates that variabels are grouped into four factors, namely motivation factor, psychology factor, demographic factor and education factor. The results of crosstab anaylisis and varians analysis show that respondents based on age, gender and education groups have different motivational and psychological levels.